2009
DOI: 10.1128/jvi.01678-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-Specific Gamma Interferon Enzyme-Linked Immunospot Assay Responses Targeting Specific Regions of the Proteome during Primary Subtype C Infection Are Poor Predictors of the Course of Viremia and Set Point

Abstract: It is unknown whether patterns of human immunodeficiency virus (HIV)-specific T-cell responses during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 41 publications
5
46
2
Order By: Relevance
“…2B). We have previously reported on specific Nef epitopes recognized at 12 weeks postinfection (22), and when responses were normalized, taking into account the amino acid length of the protein for each responder, Nef was the most immunogenic protein at all time points, corroborating findings of Streeck et al (48) and Masemola et al (34). The highest density of targeted peptides was embedded within the conserved central region of Nef between amino acids 52 to 171 (22).…”
Section: -Cell Responses During Early Hiv Infection 12019supporting
confidence: 72%
See 3 more Smart Citations
“…2B). We have previously reported on specific Nef epitopes recognized at 12 weeks postinfection (22), and when responses were normalized, taking into account the amino acid length of the protein for each responder, Nef was the most immunogenic protein at all time points, corroborating findings of Streeck et al (48) and Masemola et al (34). The highest density of targeted peptides was embedded within the conserved central region of Nef between amino acids 52 to 171 (22).…”
Section: -Cell Responses During Early Hiv Infection 12019supporting
confidence: 72%
“…Viral load was measured with the COBAS Amplicor HIV-1 monitor test, version 1.5 (Roche Diagnostics, Branchburg, NJ), and the CD4 ϩ count was measured by flow cytometry. The studied subjects were estimated to have been infected for a median duration of 6 weeks, ranging from 2 to 15 weeks postinfection at enrollment (22). The median plasma viral load at enrollment was 75,600 HIV RNA copies/ml (range, 547 to 5,510,000), and the median CD4 ϩ count was 494 cells/mm 3 (range, 197 to 989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, HIV-1 Nef was reported to be the single most immunogenic protein of HIV-1, inducing CTL responses in 91.3% of individuals across four different human ethnicities (17). In a different study, Nefassociated responses were found to be the most dominant at 12 wk postinfection (18). These findings further suggest that in most individuals, Nef-derived peptides are properly processed and presented on the surfaces of infected cells.…”
supporting
confidence: 49%